Mathematics in the Malay world prior to the arrival of western mathematics - Ismail, Mat Rofa; Mohd Atan, Kamel Ariffin (Elsevier, 2010)
The Malay world comprises the modern day Indonesia, Malaysia, Brunei, Singapore, Philippines, Thailand and Kampuchea. The subject of mathematics was taught and studied in this region in conjunction with other branches of knowledge especially those that are related to the Islamic jurisprudence, before the arrival of western mathematics. Islamic mathematics came into the Malay world through the efforts of religious scholars from this part of the world that had gone to the Middle East to study theology. They mastered the mathematics of the day in its original form in an integrated manner with branches of theology. Whatever was learnt in the Middle East was brought back and disseminated to students in the traditional schools. Among the works collected and brought back were reference books on a variety of branches of mathematics especially from Makkah, Madinah and al-Azhar University. They became the references for the teachers in imparting their mathematical knowledge to their students. The serious efforts and quality of works of the early Malay scholars in the field of mathematics can be gleaned through the few manuscripts that have survived to this day.